Analysis of Judicial Reasoning in Illegal Land Disputes (a Study of Decision Number 123/Pdt.G/2022/PN Palu) - Ferdi Ahmad Ferdi Hasan; Sulistina Sulistina (CV Edujavare Publishing, 2026)
Land disputes are among the most common civil cases in Indonesia due to overlapping ownership, control, and utilization of land rights. One form of dispute involves the unauthorized use of privately owned land as a public cemetery, as reflected in Decision Number 123/Pdt.G/2022/PN Palu. This study aims to analyze the legal reasoning (Ratio decidendi) employed by the judges in resolving the dispute and to assess whether the decision conforms to the principle of legal certainty within Indonesian land law. This research applies a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials include court decisions and statutory regulations, while secondary legal materials consist of legal literature and scientific journals. The findings indicate that the judges' legal reasoning was based on the plaintiff's ownership evidence, the fulfillment of the elements of unlawful acts under Article 1365 of the Indonesian Civil Code, and the assessment of documentary evidence and witness testimony. The decision provides legal protection for land ownership rights and reflects the principle of legal certainty because it is grounded in positive law and facts established during the trial. However, the implementation of the judgment continues to face social challenges since the disputed land has already been utilized as a cemetery.